PENGARUH KESADARAN, PELAYANAN FISKUS TERHADAP KEPATUHAN WP YANG DIMODERASI KONDISI KEUANGAN - Adistyaloka, Vivi Adeyani Tandean, Yoanda (Jurnal Akuntansi, 2015)
Tax is one of the main internal and the biggest revenue for the state, which its acceptance strongly influenced by compliance. However, the fact that the high level of non-compliance is done by a particular taxpayer taxpayer individual entrepreneurs, it is necessary to note the factors that influence taxpayer compliance.   Compliance is subject or obedient to the teachings or rules. In taxation, compliance can be defined as a state where the taxpayer fulfills all tax obligations and implement taxation rights. Factors that may be considered to affect the individual taxpayer compliance entrepreneurs including the factor of awareness of the taxpayer, the taxpayer's perception about the quality of service tax authorities, and financial condition.   The research method used in this study is a descriptive analysis of the survey approach. Independent variabel in this study is the awareness of the taxpayer and the taxpayer's perception about the quality of service tax authorities. The dependent variabel is taxpayer’s compliance, while moderating variabel is financial condition. Sampling method that used was simple random sampling of 100 respondents. Measuring instruments used in the study are Likert Scale. Testing is done is a classic assumption test, multiple regression analysis and moderated regression analyze.  The results of the F test and t test before moderated on the variabel awareness taxpayers and taxpayer perceptions about the quality of service tax authorities on taxpayer’s compliance have no significant effect but after moderated by the financial condition becomes positively significant effect on the taxpayer awareness and negatively to the perception taxpayers on the quality of service tax authorities. This suggests that the financial condition variabels proved to be a moderating variabel.  Suggestions that can be submitted, the Tax Office should be able to consider other factors such as knowledge of tax, tax penalties, and perceptions of the effectiveness of the tax system as well as considering the financial condition of the taxpayer. Keywords: Awareness of the taxpayer, financial condition, taxpayer’s compliance